SENI PERTUNJUKAN SEBAGAI ATRAKSI WISATA BUDAYA DI KECAMATAN KARIMUN KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Monariyanti, Nelvi; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research purposed to get know how performing arts development in The Karimun District of Karimun Regency Riau Island Province. How far potential and readiness from the government and the peoples to packing the perfoming arts to be a cultural tourism attraction that worthy presented for tourists. Because so far Karimun District is an area that active in performing arts events every years.This research used qualitative desciptive method to analyze the problems. The sample in this research are 11 samples by using snowball sampling. And then the technique to collected data in this research are using by observation, interview and documentation.Based on the research, performing arts packed as a cultural tourism attraction can be said to begin to develop. Because in Karimun District, performing arts presented as free entertainment for the peoples and tourists. Performing arts which consist of Dance, Music and Theatre had met several points of characteristic features for performing arts that packged for tourists as tourist community, such that a clone of the original, a short and solid version, had eliminated its sacred, magical and symbolic value, varied served, interested served. Even the last point that low pocket costs for tourist, it could be said not apply in Karimun. Because in Karimun District didn’t apply performing arts by using tickets or charge. So for every tourist who wants watched performing arts can get it free.maybe in the future can be develop performing arts attraction that worth of profit.Key words : Performing Arts, Cultural Tourism Attraction, Karimun District